Essays on the Languages, Literature, and Religion of Nepál and Tibet Together with Further Papers on the Geography, Ethnology, and Commerce of Those Countries - Hodgson, Brian Houghton (Cambridge library collection. Perspectives from the Royal Asiatic Society, 1874)
An English civil servant who worked in British India and Nepal, Brian Houghton Hodgson (c.1801–94) was also a specialist in Tibetan Buddhism. First published in 1874, this is a collection of his essays on nineteenth-century Nepal and Tibet, earlier versions of which had appeared in the Journal of the Bengal Asiatic Society and two books of Hodgson's own, later updated for the Phoenix, a monthly magazine for China, Japan and eastern Asia. Diverse in coverage, the essays represent over thirty years' research. Those in Part 1 focus on Buddhism, covering religious practices, writing, literature, attitudes to Buddhism and the differences between Buddhism and Shaivism. The pieces in Part 2 explore other aspects of Nepal and the Himalayas, such as tribal culture, colonisation and commerce. Discussing a range of linguistic, cultural, sociological and economic topics, this collection remains relevant to scholars working in these fields